SUBJEKTINIŲ TEISIŲ PRIGIMTIES PROBLEMA ŠIUOLAIKINĖSE TEISINIO POZITYVIZMO TEORIJOSE. - Baltrimienė, Milda (Problems / Problemos, 2017)
This article analyses the conceptions of individual rights presented in contemporary theories of legal positivism. Two dominant positivist conceptions of legal rights are distinguished: will theories and interest theories. The author seeks to prove that the separation thesis and other crucial premises of legal positivism lead to the conclusion that the concept of individual rights in theories of legal positivism is unnecessary and redundant. Because of this reason both will and interest theories in order to justify a certain conception of individual rights either are inevitably confronted with contradictions, or deviate from the core premises of legal positivism. In addition, the author aims to prove that active debate between will and interest theories is caused by priorities given to different conceptions of wellbeing. This means that, in the aspect of individual rights, legal positivism cannot isolate itself from content-based evaluations.